MG-126 A de novo truncating mutation in the chromatin remodeler chd8 in a patient with autism, macrocephaly and overgrowth. (4th December 2015) - Au, PY Billie; Smith, Christopher S; Lamont, Ryan E; Racher, Hilary E; Parboosingh, Jillian S; Bernier, Francois; Innes, A Micheil
Abstract : Background: CHD8 is one of a few genes in which de novo loss of function mutations have been identified in multiple cases across multiple autism cohorts in recent extensive exome sequencing studies. CHD8 is an ATP-dependent chromodomain helicase involved in chromatin remodelling and regulation of Wnt/beta-catenin and p53 pathways, which are pathways that have been implicated in non-syndromic and syndromic autism and intellectual disability. Objectives: We will describe a patient with autism and intellectual disability with a novel CHD8 mutation. We also review the phenotype of previously reported patients with CHD8 loss of function mutations. Methods: Exome sequencing of the proband and parents was used to identify de novo variants using the trio approach. A PubMed-based literature search identified other reported patients. Results: Our patient has a de novo truncating CHD8 mutation (c.4342C >T, NM_020920). He is macrocephalic (>+3SD), and has extremely tall stature with proportionate weight  (>+7SD), suggestive of an overgrowth phenotype. Other patients with CHD8 mutations that have been reported in the literature also have macrocephaly and a tendency to taller stature. Conclusions: CHD8 mutations may cause syndromic autism. Further delineation of this phenotype will be helpful for diagnostic and prognostic guidance in the future. The association of a truncating CHD8 mutation with macrocephaly and overgrowth is particularly interesting since other disorders of chromatin remodelling implicated in the Wnt/beta-catenin pathway, such as Coffin-Siris and Weaver syndromes, also have abnormal neurodevelopment associated with altered head size and in some instances generalised overgrowth.